2018
DOI: 10.1080/15332640.2018.1494658
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Insomnia Severity Index in Ethiopian adults with substance use problems

Abstract: This study investigated the psychometric properties of the Insomnia Severity Index (ISI) in substance-using Ethiopian adults. A simple random sampling of houses and a purposive sampling selection was performed in Mizan city, Ethiopia (n = 406). Participants completed the ISI and a meta-cognition questionnaire and sociodemographic information. IBM SPSS software with Amos was used for data analysis. There was no major ceiling or floor effect in the ISI scores. The internal consistency (Cronbach's alpha = 0.68 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This could be due to the fact that khat chewing causes sleep disturbance [33] as a result, chewers would use alcohol for better sleep. However, different studies showed concurrent use of khat, cigarette, and alcohol would result in sleep deprivation [32,34,35]. Therefore, giving due attention is needed to minimize the concurrent effect of khat, alcohol, and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the fact that khat chewing causes sleep disturbance [33] as a result, chewers would use alcohol for better sleep. However, different studies showed concurrent use of khat, cigarette, and alcohol would result in sleep deprivation [32,34,35]. Therefore, giving due attention is needed to minimize the concurrent effect of khat, alcohol, and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This study has a significant implication for the public and policymakers. Khat chewing in the community could affect social life [24], the economy [27], and result in poor health outcomes [35][36][37][38]. Currently, in Ethiopia farmers in the rural area are expanding the cultivation of khat and the landmass covered by cereals and fruits is decreasing from time to time.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that Dragioti et al [54] proposed a four-item version (items 2, 4, 5, 7), especially for patients with chronic pain. However, three studies reported the 2-factor solution [58][59][60] (Severity of sleeping difficulties with items 1-4 or alternatively items 1a, 1b, 1c, and 2; Impact of insomnia with items 5-7 or, alternatively, items 3-5). This solution generally explained 61.80% of variance with mean factor loadings ranging from 0.50 to 0.90 for both factors and mean inter-factor correlation of 0.50 (Table 2).…”
Section: The Sleep-disorder Scalesmentioning
confidence: 99%
“…Insomnia was measured using ISI, which is a seven-item selfreport questionnaire evaluating the nature, severity, and impact of insomnia. The scores range from normal (0-7), sub-threshold (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), to severe (22 and above) (22). The psychological distress of COVID-19 was measured using the IES-R, which contains 22-items.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%